Barthel Index as a Predictor of Mortality in Patients with Acute Coronary Syndrome: Better Activities of Daily Living, Better Prognosis - Li F (Dove Medical Press, 2020)
Fanghui Li,1,* Dongze Li,1,* Jing Yu,2 Yu Jia,1 Ying Jiang,1 Tengda Chen,1 Yongli Gao,1 Zhi Wan,1 Yu Cao,1 Zhi Zeng,1 Rui Zeng1,3 1Department of Emergency Medicine and Laboratory of Emergency Medicine, Deep Underground Space Medical Center, West China Hospital, and Disaster Medical Center, Sichuan University, Chengdu, People’s Republic of China; 2West China School of Nursing, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 3Department of Cardiology, West China Hospital, Sichuan University, Chengdu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Rui ZengDepartment of Cardiology, West China Hospital, Sichuan University, 37 Guoxue Road, Chengdu 610041, Sichuan, People’s Republic of ChinaTel +86-28-85423248Fax +86-28-85582944Email zengrui_0524@126.comBackground: The Barthel index (BI) is a widely used assessment tool for evaluating physical performance in activities of daily living (ADL). The association between BI scores and mortality in hospital and during follow-up of acute coronary syndrome (ACS) patients remains unclear. The present study investigated whether the BI score could be used as a predictor for mortality of ACS.Methods: We investigated ACS patients from the multi-center Retrospective Evaluation of Acute Chest Pain (REACP) study. The association between BI scores and all-cause mortality of patients with ACS was analyzed by Cox proportional hazards models. The primary endpoint was all-cause death and the secondary endpoint was cardiac death during follow-up.Results: Among 2908 patients with ACS enrolled, 277 (9.5%) patients died within a median follow-up time of 10.6 months. Patients with lower BI had higher risks of mortality, compared with those with higher BI in ACS patients. Kaplan–Meier analysis revealed that patients with lower BI had worse survival rates than patients with higher BI (P < 0.001). After adjustment for potential influencing factors, multivariate Cox regression analysis showed that the BI was independently associated with all-cause mortality and cardiac mortality, respectively.Conclusion: The BI at admission has the powerful potential to provide useful prognostic information of early risk stratification, and routine recording of the BI at the ED visit may help in decision-making and health care planning for patients with ACS.Keywords: Barthel index, activities of daily living, acute coronary syndrome, prognosis, mortality